Comparison between Double and Triple Exponential Smoothing Methods for Forecasting Poverty Rate of Yahukimo Regency in 2025-2030 - Agustinus Langowuyo; Felix Reba; Yosefina Sarena (Jurnal Sains Dasar, 2022)
Currently, the government faces so many issues, one of which is poverty. However, it is not a new thing since many other countries also face this classic issue. Poverty, from an economic point of view, is measured by the people's inability to meet basic needs for food, not food in terms of expenditure. Based on data released by the Central Statistics Agency (BPS) regarding poverty rates in Indonesia, several areas are included in the highest poverty rates including East Nusa Tenggara, Maluku, Gorontalo and Papua. The poverty rates for this region are 21.21%, 17.99%, and 15.99%, respectively. In this regard, Papua has the highest poverty rate of the three provinces. According to BPS, the three poorest districts in Papua Province in 2017 included Deiyai Regency at 43.63%, Intan Jaya Regency at 42.23% and Yahukimo Regency at 39.33%. This study aimed to predict the poverty rate of Yahukimo district in 2025-2030. This research employed Double and Triple Exponential Smoothing methods. It used secondary data, namely data related to the poverty rate in Yahukimo Regency in percent (%) in 2003-2019. The results showed that the poverty rate data in 2025-2030 were 36.48%, 36.09%, 35.7%, 35.31%, 34.92% and 34.53% respectively. In other words, the poverty rate in Yahukimo Regency had decreased compared to previous years.